Optimization of the process parameters for stabilization and improvement of the turning process capability - Cerce, Luka; Kramar, Davorin; Borojević, Stevo (Journal of Production Engineering, 2018)
The paper deals with a narrow tolerances turning process. A statistical process control (SPC) on the existent machining process showed that the process was not stable and incapable. Before the machining process analysis a measurement system analysis (MSA) of the applied measuring system has been performed. In order to stabilize the process the machine tool linear axis calibration has been performed. The stability and capability of the machining process increased but the problem of the roundness was still present. The possible process parameters, which could affect the roundness, were examined with the design of the experiment methodology (DOE). The results showed that the clamping force has the largest effect. Therefor a new clamping fixture was suggested to eliminate the roundness problem.